Study on the Cordyceps militaris Cultivation in Differential Media and Substrates Formulation: https://doi.org/10.69692/SUJMRD090101 - Sibounnavong, Phoutthasone; Phialathounheuane, Khonesavanh; Xasydavong, Nuttaya; Luangphan, Jhonny; Hiumphasong, Vaen; Phimmavongsa, Keolavanh; Sibounnavong, Phonesavard (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The study was study on the Cordyceps militaris Cultivation in Differential Media in plant diseases and weeds laboratory, Faculty of Agriculture, National University of Laos. The experiment was conducted for six months. This is of study have two parts, part one to testing fibers of growing Cordyceps militaris in Differential Media and Substrates Formulation. The experiment was set up as Completely Randomized Design (CRD) layout was used with four replications and three treatments as they are: T1 PDA (control), T2 supplements one + Silk worm pupae, T3 supplements two + egg. To testing fibers of growing Cordyceps militaris in three kind differentials of twenty days had different significant (P<0.05), T2 have medium testing fibers of growing Cordyceps militaris with amount of 8.71 cm, by T3 is 8.32 cm, the lowest by T1 8.06 cm, and to notice T2 have dark orange in color colony, by T3 and T1 light color yellow. Part two to testing substrates and supplements Cordyceps militaris in three kind differentials to yield. The experiment was arranged in a Completely Randomized Design (CRD) layout was used with four replications and five treatments as they are: T1 Rice bean + potato dextrose broth PDB (control), T2 Rice rations + potato dextrose broth (PDB), T3 Rice bean + liquid broth Silk worm pupae 30 gram, T4 Rice bean + liquid broth Silk worm pupae 60 gram, T5 Rice rations + liquid broth Silk worm pupae 60 gram. The study was use twenty-four. The results found that there are different significant (P<0.05), T4 fibers of growing Cordyceps militaris by 5.93 days,by T5, T3and T2 is 6.25, 8.00 and 10.18 days respectively. By T1 is 10.00 days. The developmenting of fibers to substitute flower mushroom in 5 treatments. The results found that there are different significant (P<0.05), T5. The developmenting of fibers to substitute flower mushroom 22.18 days, by T2, T3 and T4 is 28.56, 25.06 and 21.81 days respectively. T1 is 29.31 days. However, weight flower mushroom T5 weight 27.25 gram/glass, by T4, T3 and T1 weight 26.88, 23.44 and 18.13 gram/glass respectively. By T2 weight 17.81 gram/glass.